PENERAPAN BIMBINGAN BERKELANJUTAN BAGI SISWA UNTUK MENINGKATKAN PEMAHAMAN TERHADAP BAHAYA BULLYING DI KELAS XII IS1 SMA NEGERI 2 MAUMERE - THEODOSIA THEORILDE DGAMES, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to investigate the dangers of bullying through increased understanding of classroom guidance on twelve grade students of SMA Negeri 2 Maumere Academic Year 2018/2019. This study uses the classroom action research. Subjects in this study were 33 students. Data collection instruments used in the form of a questionnaire. Data analysis technique to examine differences between the mean pretest and posttest after the act of using a t-test. The results showed that after being given a classical guidance services, understanding the dangers that are in the category of very high that the number of frequency of 23 by 69,69%. In the category of very high already reached more than half the number of students. In the high category with a number of frequencies 6, 18, 75%, moderate category frequency number 3 for 9, 375%, the low category number 0 of 0%, the category of very low with the number of frequencies 0 of 0%. Thus, it can be concluded that the classical guidance is effective and innovative strategies to improve the understanding of twelve grade students of SMA Negeri 2 Maumere on understanding the dangers of bullying. The results of this study can be used as reference material for the teacher guidance and counseling to improve understanding of the dangers of bullying on students through classical counseling services in schools.